A cross sectional study of cardiopulmonary complications and severity of pulmonary hypertension and lung fibrosis in patients with systemic sclerosis - Wan Ali, Wan Ahmad Syahril Rozli; Mohamed Said, Mohd Shahrir; Shaharir , Syahrul Sazliyana; Ban , Andrea Yu Lin; Hussain, Rizuana Iqbal; Rosman, Azmillah (Turkish League Against Rheumatism, 2015)
Objectives: This study aims to identify the characteristics of scleroderma patients in terms of sociodemographic and clinical characteristics and severity of lung fibrosis and pulmonary hypertension and to show the association between European Scleroderma Study Group (EScSG) scoring and severity of pulmonary hypertension and lung fibrosis.